Comparative assessment of birth preparedness and complication readiness among women in rural and urban areas of Bangladesh (Bioresearch Communications, 2022)
Background: Birth preparedness and complication readiness is an imperative intervention which has proven to reduce delays in care seeking behavior in case of obstetric emergencies. Although, many pregnant women and their families do not take the suggested steps to prepare for childbirth, despite of being known of them. Additionally, marked disparities often have been observed between rural and urban areas, with more maternal and neonatal deaths occurring in the rural areas owing to the unpreparedness. This study thus set out to assess and compare the knowledge, practice and factors associated with birth preparedness and complication readiness among women from rural and urban areas in Bangladesh.Methodology: A cross-sectional comparative study design have been undertaken among 250 rural and 240 urban women in the Department of Obstetrics and Gynecology, Shaheed Suhrawardy Medical College and Hospital, Dhaka, Bangladesh and Shaheed Sayed Nazrul Islam Medical College and Hospital, Kishoreganj, Dhaka over a period of 6 months from 1st October 2020 to 30th March 2021. All pregnant women who attended in the antenatal clinic of SSNIMCH and SSMCH for the first time during the study period was include in the study. Quantitative data was collected by the use of semi structured questionnaires adapted from the safe motherhood questionnaire, developed by maternal and neonatal Programme of Johns Hopkins Programme for International Education in Gynaecology and Obstetrics (JHPIEGO) an affiliate of John Hopkins University.Result: Birth preparedness and complication readiness was evident in 34.17% of the urban and 30.4% of the rural respondents. Urban women were statistically significantly more aware of the danger signs of pregnancy, labour and postpartum period (p